Investigating the effect of various methods of soaking from Vicia ervilia in water and alkaline, acid and salt solutions on reduction of anti-nutritional compounds (International Journal of Biology and Chemistry, 2019)
Vicia (V.) ervilia, commonly termed as bitter vetch, produces grains belonging to legumes family. One of the factors limiting the usage of V. ervilia is the existence of large amounts of anti-nutritional factors in the grains thereof. Considering the importance of the anti-nutritional factors, the present study investigated the effect of different methods of soaking from V. ervilia grains on the reduction of antinutritional factors rates. All of the soaking methods were found considerably reducing the anti-nutritional factors rates in all treatments as compared to V. ervilia grain flour. It was also found out in the present study that alkaline treatment, provides for the highest reduction of hydrolysable and dense tannin, phenolic ingredients in contrast to the other methods. Moreover, considerable increase in canavanine ooze-out from V. ervilia was documented for aqueous and saline treatments. Among different treatments, the highest reduction in total phenolic compounds and tannins was observed in alkaline maceration, followed by acidic, aqueous and salt saline. Also the lowest amount of canavanine was observed in aqueous treatment and the highest amount in alkaline treatment. The results show that treatment method can be selected depending on the type of need to remove anti-nutritional compounds of V. ervilia seeds. So soaking in water and use of saline solutions is preferred to soaking in basic and acidic solutions for the latter damages to some nutrients under basic and acidic conditions.